Conceptual Studies Of Biobased Fabrication Of Silver Nanoparticle And Its Delivering Pathway Analysis Inside The Breast Cancer HER2 Protein (Journal of Pharmaceutical Negative Results, 2023)
Breast cancer is one of the most common malignancies among women globally, posing a major public health burden. This study primly aimed to theoretically prove the formation of silver nanoparticles by Dimocarpus longan fruit phytoconstituents and the targeted delivery of phytoconstituent by silver nanoparticles inside the cavity of the HER2 protein. The algorithm adsorption location and CHARMm-based docking were used to find the interaction between atoms of 9 phytoconstituents and active site amino acids, respectively. The result of the adsorption locator revealed that silver metal atom π and metal acceptor type interaction with four fragments of Rutin compare to other molecules. The caped complex of silver and Rutin complex CHARMm protocol run resulted that the silver atom standing outside the protein and only the Rutin getting inside the cancer protein HER2's binding pocket formed multiple hydrogen bonds and π-alkyl interaction with the energy of -71.0249 Kcal/mol. The overall result concluded that the Rutin fabricates the silver nanoparticle and the capped silver delivers the Rutin inside the cancer protein HER2's binding pocket. Which leads to the apoptosis of breast cancer cells.